Analysis of Emina Product Endorsements on the Instagram Account @tasyafarasya for Teenagers - Haliza, Sabina Nur; Majdiyyah, Hamidah; Nurfalah, Farida; Wihayati, Welly (Indonesian Journal of Advanced Research, 2025)
Endorsement is a promotional strategy that has been widely used in the marketing world to increase attractiveness and trust in a product. This study aims to analyze @tasyafarasya's endorsement of Emina products among teenagers through Instagram. With a qualitative descriptive approach, data was collected through interviews and documentation studies using purposive sampling techniques as many as 5 informants. The results showed that @tasyafarasya succeeded in building credibility as a celebrity endorser through competence in the beauty world, honesty in providing product Emina reviews, and her attractiveness. The followers rated the shared content as very informative, transparent, and easy to understand, which encouraged them to try Emina products. These findings support the theory of source credibility by Hovland and Weiss (1951), which states that the competence, trustworthiness, and attractiveness of endorsers affect the effectiveness of the message conveyed.